Complete Hydatidiform Mole Presenting as a Placenta Accreta in a Twin Pregnancy with a Coexisting Normal Fetus: Case Report. (13th August 2012) - Aguilera, Marijo; Rauk, Philip; Ghebre, Rahel; Ramin, Kirk
Abstract : A twin pregnancy with a complete hydatidiform mole and a coexisting normal fetus (CHMF) is a rare clinical scenario, and it carries many associated pregnancy and postnatal risks. Limited numbers of case studies exist reporting an outcome of live birth, and only three prior cases report the presentation of a hydatidiform mole as a placenta previa. We report a case of CHMF with the molar component presenting antenatally as a placenta previa, which ultimately resulted in placenta accreta at the time of delivery. A live male infant was delivered at 34 weeks' gestation via planned cesarean section, and a hysterectomy was performed following unsuccessful removal of the molar component. We additionally utilized previously described methods of placing internal iliac balloons and ureteral stents prior to delivery. In such a high-risk pregnancy with a known molar previa component, these surgical preparation measures may be of benefit.